2021
DOI: 10.3389/fpls.2021.682879
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing of Small RNAs for the Sanitary Certification of Viruses in Grapevine

Abstract: Biological indexing is the method generally recognized for the certification of propagative grapevines in many countries, and it is mandatory in the European Union. It consists of the evaluation of the plant material after grafting on indicators that are inspected for symptom development. This is a lengthy process that requires well-trained workers, testing field, etc. Alternative diagnostic methods such as serology and RT-qPCR have been discarded for certification because of their intrinsic drawbacks. In turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…The automated VirusDetect package has already been used to identify viruses in grapevine, soybean, sweet potato, cherry tree, and lettuce [ 49 , 50 , 51 , 52 ]. Also, the highest number of viruses was detected in contigs assembled with k-mer = 15 in Velvet, which is consistent with previous studies [ 53 , 54 ]. Therefore, when more than one assembler or k-mer was used, the chance of identifying viruses with low concentrations or those that do not have many reads in the library increased [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…The automated VirusDetect package has already been used to identify viruses in grapevine, soybean, sweet potato, cherry tree, and lettuce [ 49 , 50 , 51 , 52 ]. Also, the highest number of viruses was detected in contigs assembled with k-mer = 15 in Velvet, which is consistent with previous studies [ 53 , 54 ]. Therefore, when more than one assembler or k-mer was used, the chance of identifying viruses with low concentrations or those that do not have many reads in the library increased [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another criterion for cross-protection that should be carefully examined is the eventual presence of other viruses in the infected host plant, potentially responsible for specific intra host virus-virus interactions that might affect the ability of the mild strain at protecting the crop [ 66 , 67 ]. This is particularly important for grapevine for which multi-infection is common generally displaying a complex virome in the field [ 20 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. With our RNA-Seq data, we showed that several viroids and viruses were present in the studied vines samples.…”
Section: Discussionmentioning
confidence: 99%
“…The sRNA method explicitly targets the products of the host antiviral response mediated by plant Dicer-like enzymes (DCLs) that cleave viral RNA and replication intermediates into 21–24 nt-long fragments (reviewed in [ 14 ]). Moreover, the reduced costs of sRNA-seq and its ability to flag actively replicating viral pathogens compared to RNA-seq have made it a widely adopted approach for viral pathogen diagnostics [ 10 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%